The Latin American Debate: Dependent Capitalism, Superexploitation, and Revolution - Osorio Gómez, Jaime (Social justice, 2013)
The author analyzes the historical and ongoing limitations of democracy and development in the context of neoliberal capitalism in Latin America. Topics discussed include negation of the presumed universal discourse of capitalist modernity by Latin America, orthodox application of neoliberal policies and Fernando de la Rua's government in Argentina. Other topics discussed include triumph of the Cuban Revolution and the book "The Development of Capitalism in Latin America" by Agustxn Cueva.